Attitudes towards spirituality and spiritual care among nursing employees in hospitals - Tanja Montanič Starc; Igor Karnjuš; Katarina Babnik (Nurses and Midwives Association of Slovenia, 2019)
Introduction: Understanding spirituality and spiritual care is a prerequisite for holistic care. The research goal was to describe nurses' attitudes towards spirituality and spiritual care. Methods: The study was carried out between 2015 and 2016 using a quantitative non-experimental method. The Spirituality and Spiritual Care Rating Scale Questionnaire was given to a sample of 182 nursing care employees, mostly women (n = 153, 88.4 %), with completed higher (n = 93, 53.8 %) or secondary (n = 75, 43.4 %) education, from four Slovenian hospitals. The questionnaire had adequate internal consistency (Cronbach alpha = 0.83). Results: The highest agreement (x = 4.27, s = 0.82) was reached on the statement which describes spiritual care as respecting patient's privacy, dignity, cultural and religious beliefs. Participants also agreed with the statement that they provide spiritual care by demonstrating kindness, care, and cheerfulness (x = 4.2, s = 0.76), but they expressed uncertainty about the statement that spirituality and spiritual care are fundamental aspects of nursing care (x = 2.88, s = 1.08). Discussion and conclusion: Participants connect spirituality with an understanding of themselves and the world, rather than only with religion and sacral objects. The research has confirmed the findings of previous Slovenian studies that nurses give priority to meeting patients' physical needs before spiritual ones probably also as a result of a lack of knowledge and professional guidance on spiritual care.